2020
DOI: 10.1161/jaha.119.015752
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration in Acute Heart Failure: Implications of Ejection Fraction and Early Response to Treatment From CARRESS‐HF

Abstract: Background Ultrafiltration is not commonly used because of higher incidence of worsening renal function without improved decongestion. We examined differential outcomes of high versus low fluid removal and preserved versus reduced ejection fraction (EF) in CARRESS‐HF (Cardiorenal Rescue Study in Acute Decompensated Heart Failure). Methods and Results Baseline characteristics in the ultrafiltration arm were compared according to 24‐hour ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In the UNLOAD trial, patients with acute HF who underwent ultrafiltration lost more weight than those on diuretic treatment, with lower readmittance rate after 90 days after hospital discharge, even though no improvement of renal function was observed [ 142 ]. Moreover, in patients with acute HF, ultrafiltration treatment was not associated with renal function worsening [ 143 ].…”
Section: Therapeutic Strategies In Crsmentioning
confidence: 99%
“…In the UNLOAD trial, patients with acute HF who underwent ultrafiltration lost more weight than those on diuretic treatment, with lower readmittance rate after 90 days after hospital discharge, even though no improvement of renal function was observed [ 142 ]. Moreover, in patients with acute HF, ultrafiltration treatment was not associated with renal function worsening [ 143 ].…”
Section: Therapeutic Strategies In Crsmentioning
confidence: 99%
“…In concordance with this study, a substudy of the CARRESS-HF (Cardiorenal Rescue Study in Acute Decompensated Heart Failure) that examined differential outcomes of high versus low fluid removal and preserved versus reduced ejection, demonstrated that in patients with HFpEF, ultrafiltration was associated with worsening renal function irrespective of fluid removal rate and higher initial fluid removal was associated with higher rates of adverse clinical outcomes, highlighting variable responses to decongestive therapy. For that reason, patients with HFpEF and resistance to diuretics and other pharmacological drugs have clinical benefits in terms of decreasing hospitalization rates with PD treatment [ 74 ]. PD is a home-based treatment that allows a gentle removal of the excess water and sodium with minimal haemodynamic changes, with a great capacity to be able to adapt the requirements according to the clinical situation and the lifestyle of the patients.…”
Section: Management Of Crsmentioning
confidence: 99%
“…Authors examined differential outcomes of high versus low fluid removal and preserved versus reduced ejection fraction (EF) in CARRESS-HF (Cardiorenal Rescue Study in Acute Decompensated Heart Failure). 66 In their study, they were able to show that in patients with acute HF, higher initial fluid removal with UF had no association with worsening renal function. 66 In patients with EF > 40%, UF was associated with worsening renal function irrespective of fluid removal rate, and higher initial fluid removal was associated with higher rates of adverse clinical outcomes, highlighting variable responses to decongestive therapy.…”
Section: Introduction: Pathophysiology and Rationale Of Ultrafiltrationmentioning
confidence: 95%
“…66 In their study, they were able to show that in patients with acute HF, higher initial fluid removal with UF had no association with worsening renal function. 66 In patients with EF > 40%, UF was associated with worsening renal function irrespective of fluid removal rate, and higher initial fluid removal was associated with higher rates of adverse clinical outcomes, highlighting variable responses to decongestive therapy. 66 So, clearly, there is no unanimity about the usefulness of UF in HF.…”
Section: Introduction: Pathophysiology and Rationale Of Ultrafiltrationmentioning
confidence: 95%